Predictors of Mortality in Patients with Infections Due to Carbapenem-Resistant Gram-Negative Bacteria - Hector Orlando Rivera-Villegas; Bernardo Alfonso Martinez-Guerra; Rosalia Garcia-Couturier; Luis Fernando Xancal-Salvador; Veronica Esteban-Kenel; Ricardo Antonio Jaimes-Aquino; Miguel Mendoza-Rojas; Axel Cervantes-Sánchez; Steven Méndez-Ramos; Jorge Eduardo Alonso-Montoya; Diana Munguia-Ramos; Karla Maria Tamez-Torres; et al. (MDPI AG, 2023)
Introduction: Infections caused by carbapenem-resistant Gram-negative bacteria (CR-GNB) are a significant cause of mortality and represent a serious challenge to health systems. The early identification of mortality predictors could guide appropriate treatment and follow-up. We aimed to identify the factors associated with 90-day all-cause mortality in patients with CR-GNB infections. Methods: We conducted a cohort study from 1 January 2019 to 30 April 2022. The primary outcome was death from any cause during the first 90 days after the date of the first CR-GNB-positive culture. Secondary outcomes included infection relapse, invasive mechanical ventilation during follow-up, need for additional source control, acute kidney injury, Clostridioides difficile infection, and all-cause hospital admission after initial discharge. Bivariate and multivariate Cox-proportional hazards models were constructed to identify the factors independently associated with 90-day all-cause mortality. Results: A total of 225 patients with CR-GNB infections were included. Death occurred in 76 (34%) cases. The most-reported comorbidities were immunosuppression (43%), arterial hypertension (35%), and COVID-19 (25%). The median length of stay in survivors was 18 days (IQR 10-34). Mechanical ventilation and ICU admission after diagnosis occurred in 8% and 11% of cases, respectively. Both infection relapse and rehospitalisation occurred in 18% of cases. C. difficile infection was diagnosed in 4% of cases. Acute kidney injury was documented in 22% of patients. Mechanical ventilation after diagnosis, ICU admission after diagnosis, and acute kidney injury in the first ten days of appropriate treatment were more frequently reported among non-survivors. In the multivariate analysis, age (HR 1.19 (95%CI 1.00-1.83)), immunosuppression (HR 1.84 (95%CI 1.06-3.18)), and septic shock at diagnosis (HR 2.40 (95% 1.41-4.08)) had an independent association with death during the first 90 days after the CR-GNB infection diagnosis. Receiving antibiogram-guided appropriate treatment was independently associated with a lower risk of death (HR 0.25 (95%CI 0.14-0.46)). Conclusions: The presence of advanced age, immunosuppression, septic shock at diagnosis, and inappropriate treatment are associated with higher 90-day all-cause mortality in hospitalised patients with infections due to CR-GNB. Recognition of the risk factors for adverse outcomes could further assist in patient care and the design of interventional studies that address the severe and widespread problem that is carbapenem resistance.